The impact of infrastructure planning in spatial plans on carrying capacity assessment in mountain tourist areas - Đorđević Dejan S.; Šećerov Velimir; Filipović Dejan; Lukić Bogdan (Spatium, 2016)
This paper analyses the impact of infrastructure planning on carrying capacity assessment in mountain tourist areas, aiming to define the procedure, as well as to present an algorithm that could enable the application of carrying capacity methods in the process of developing planning documents. This would, in addition to the common practice of the hitherto used research methods, pay appropriate attention to the impact of infrastructure systems. In this regard, the paper first presents the basic theoretical and methodological problems of carrying capacity assessment, and then it considers the basic characteristics of evaluating carrying capacity in mountain tourist areas. Following this is a review of the basic principles of infrastructure planning, which gives practical recommendations for the infrastructure planning process in mountain tourist areas, with a particular emphasis on the impact of infrastructure on carrying capacity assessment. The example of Tara National Park, a mountainous area in Serbia which served as a place for verification of this procedure, shows the need to review the current planning solutions defined for this protected area.